Culinary waste management for a healthier planet: a qualitative study - Chin Choo Yap; Shin Ling Wu; Pau Voon Soon; Elizaveta Berezina; Mohamed Kheireddine Aroua; Lai Ti Gew (Cogent Social Sciences, 2024)
The burgeoning food waste problem is driving environmental pollution and climate change due to landfilling of waste. It is imperative to reduce greenhouse gas emissions and lower carbon footprint through food waste management. In the culinary setting, a vast amount of food waste is generated from food preparation. However, there is no module to educate staff on this. In this study, a culinary waste management (CWM) module was introduced to train culinary arts students to reduce culinary waste in the food preparation process, from cleaning to assembling. It is essential to assess the user-friendliness of the module during practical implementation. This study aimed to explore participants’ awareness and understanding of CWM before and after implementing of a CWM module in teaching kitchens and identify the motivators and barriers to its implementation. A total of 35 participants, consisting of students, teaching chefs and cleaning staff’s were recruited at Sunway University, Malaysia. Themes derived in the pre-module interview revealed a varying degree of engagement among participants, with low literacy, alongside barriers like labor-intensiveness and concern over hygiene. The post-module interview highlighted positive psychological and cognitive impacts on participants with motivators that drive them to practice CWM. Nevertheless, barriers such as resistance to novelty impeded the implementation. Therefore, CWM is the way forward to reduce the significant amount of waste generated in culinary settings. Integrating this CWM module into the education-industrial system will equip future culinary professionals with the knowledge and skills needed for.g a sustainable culinary career.